2006
DOI: 10.1142/s0217751x06033830
|View full text |Cite
|
Sign up to set email alerts
|

NJL Interaction Derived From QCD

Abstract: We apply Bogolubov approach to QCD with two light quarks to demonstrate a spontaneous generation of an effective interaction, leading to the Nambu -JonaLasinio model. The resulting theory contains two parameters: average low-energy value of α s and current light quark mass m 0 . All other low-energy parameters: the pion decay constant, mass of the π-meson, mass of the σ-meson and its width, the constituent quark mass, the quark condensate are expressed in terms of the two input parameters in satisfactory corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(103 citation statements)
references
References 27 publications
3
98
0
2
Order By: Relevance
“…In the same way as in work [9] we start from the standard Lagrangian of QCD with two light quarks and number of colours N = 3…”
Section: Compensation Equation For Effective Form-factormentioning
confidence: 99%
“…In the same way as in work [9] we start from the standard Lagrangian of QCD with two light quarks and number of colours N = 3…”
Section: Compensation Equation For Effective Form-factormentioning
confidence: 99%
“…Bogoliubov compensation principle [4,5]. In works [6][7][8][9][10], this approach was applied to studies of the spontaneous generation of effective non-local interactions in renormalizable gauge theories. The approach is described in detail in a recent book [11].…”
Section: Effective Three-graviton Interactionmentioning
confidence: 99%
“…In this section, we consider a model for such running in view of obtaining an impression, if such searches are advisable. Now, previous experience [6][7][8][9][10][11][12][13][18][19][20][21] has shown that solutions of compensation equations are usually expressed in terms of Meijer functions [14]. Thus we use these useful functions in our attempts here.…”
Section: A Model For a Running Gravity Couplingmentioning
confidence: 99%
“…Отметим, что аналогичное приближение было использовано в работах [2], [3], [5] при изучении спонтанного возникновения взаимодействия вида Намбу-Йона-Лази-нио. Было показано, что результаты согласуются с экспериментальными данными со средней точностью ∼ 10 − 15%.…”
Section: уравнение компенсации для аномального трехбозонного взаимодеunclassified
“…Спонтанное возникновение взаи-модействия вида Намбу-Йона-Лазинио рассматривалось в работах [2], [3], [5], при-чем в результате получено вполне успешное описание низкоэнергетической адрон-ной физики, включая значения m π , f π , m σ , Γ σ , ⟨qq⟩, M ρ , Γ ρ , M a1 , Γ a1 , на основе исходных параметров квантовой хромодинамики.…”
Section: Introductionunclassified